Ambiguitas Status Hukum Dokter dalam Perjanjian Terapeutik: Analisis Kritis terhadap Perlindungan Hukum dalam Sengketa Medis - Heri Heriyanto (Jurnal Hukum Lex Generalis, 2026)
In Indonesia, the legal relationship between doctors and patients is fundamentally constructed as a therapeutic contract based on the principles of civil law. However, in practice, doctors often provide medical services within an institutional framework, such as hospitals, so that their status can simultaneously be positioned as that of an employee or a professional based on a specific employment relationship. This dual position creates ambiguity in determining legal liability when medical disputes arise. Although various studies have addressed medical liability and patient protection, research that critically analyzes the ambiguity of doctors’ legal status within therapeutic agreements and its implications for legal protection in medical disputes remains relatively limited. This study aims to analyze the ambiguity of doctors’ legal status in therapeutic agreements and to examine its implications for legal protection mechanisms in the resolution of medical disputes. The research method used is normative legal research employing a statutory approach and a conceptual approach. Legal materials were systematically analyzed to identify inconsistencies between civil law, criminal law and medical practice regulations. The research findings indicate that the therapeutic agreement is essentially a contractual relationship between the physician and the patient based on trust and professional standards. However, when a physician acts within an employment relationship with a hospital, issues arise regarding the allocation of legal liability whether it rests with the physician personally, the hospital as the employer, or both jointly. This ambiguity has the potential to undermine legal certainty and affect the protection of both patients’ rights and the rights of medical personnel. Therefore, regulatory harmonization is necessary to ensure a balance of legal protection and uphold the principle of procedural justice in the resolution of medical disputes.